Voices in displacement - Meyerhoefer, C (Refugee Studies Centre, University of Oxford, 2015)
“These people are as if lost in time and space.” Still displaced after 20 years, residents of collective centres in Bosnia and Herzegovina share their frustration. They need to be listened to.